THE ROLE OF ABU RAYKHAN BIRUNI’S ATHAR UL-BAQIYA’ IN THE ISLAMIC CIVILISATION (Western European Journal of Historical Events and Social Science, 2025)
Abu Raykhan Beruni is important in the advancement of Science with his famous works. In this article highlights of the role of Abu Raykhan Biruni’s Athar ul-Baqiya’ in the islamic civilisation